The biological function and clinical significance of SF3B1 mutations in cancer - Zhixia Zhou; Qi Gong; Yin Wang; Mengkun Li; Lu Wang; Hongfei Ding; Peifeng Li (BMC, 2020)
Abstract Spliceosome mutations have become the most interesting mutations detected in human cancer in recent years. The spliceosome, a large, dynamic multimegadalton small nuclear ribonucleoprotein composed of small nuclear RNAs associated with proteins, is responsible for removing introns from precursor mRNA (premRNA) and generating mature, spliced mRNAs. SF3B1 is the largest subunit of the spliceosome factor 3b (SF3B) complex, which is a core component of spliceosomes. Recurrent somatic mutations in SF3B1 have been detected in human cancers, including hematological malignancies and solid tumors, and indicated to be related to patient prognosis. This review summarizes the research progress of SF3B1 mutations in cancer, including SF3B1 mutations in the HEAT domain, the multiple roles and aberrant splicing events of SF3B1 mutations in the pathogenesis of tumors, and changes in mutated cancer cells regarding sensitivity to SF3B small-molecule inhibitors. In addition, the potential of SF3B1 or its mutations to serve as biomarkers or therapeutic targets in cancer is discussed. The accumulated knowledge about SF3B1 mutations in cancer provides critical insight into the integral role the SF3B1 protein plays in mRNA splicing and suggests new targets for anticancer therapy.